Dental Amalgam Waste in Dentistry: Sources, Environmental Impact and Management Strategies - Konakanchi, Anusha; Alla, Rama Krishna; Rao, Savitha P; Kandikantla, Pradeep; Ganta, Gopala Krishna; Vallabhaneni, Saketha (International Journal of Dental Materials, 2025)
Among the restorative materials, dental amalgam is one of the most commonly used due to its superior characteristics, including clinical durability, affordability, and clinically reliable properties. However, its mercury content has raised environmental concerns, especially regarding the waste generated during routine procedures such as placing, removing, finishing, and replacing old amalgam restorations. This waste can enter dental wastewater systems through plumbing and suction, which is why dental clinics are such an important source of mercury for municipal wastewater treatment plants, even though dentistry only contributes a small amount of global anthropogenic mercury emissions. Once released, amalgam particles can build up in sewage sludge or enter water bodies. Mercury can turn into methylmercury and accumulate in living things, which is considered the most hazardous for the environment and public health. As a result, various regulatory bodies have set guidelines to limit the amount of mercury that can be released from dental offices. Best management practices, including separating waste, recycling, and using ISO-certified amalgam separators, have been shown to significantly lower the amount of mercury released. This review provides insights into the recent information regarding the sources of amalgam waste, its effect on the environment, the regulatory framework, and ways to manage it. It also emphasizes how important it is for dental professionals to use environmentally friendly methods to reduce the environmental impact of dental amalgam.